Results on common fixed points - Zeqing Liu; Jeong Sheok Ume (International Journal of Mathematics and Mathematical Sciences)
We establish common fixed point theorems related with families of self mappings on metric spaces. Our results extend, improve, and unify the results due to Fisher (1977, 1978, 1979, 1981, 1984), Jungck (1988), and Ohta and Nikaido (1994).